Decision Support for Patients: Values Clarification and Preference Elicitation. (February 2013) - Llewellyn-Thomas, Hilary A.; Crump, R. Trafford
Providing a patient with decision support involves helping that person to choose among two or more elective health care options. "Values Clarification" and "Preference Elicitation" are integral to the full decision-support process. During values clarification, the patient and clinician gain insight into the importance that the patient ascribes to the options' positive and negative characteristics. During preference elicitation, the patient identifies which options are, overall, personally most favored (and, by corollary, which are least favored). This article identifies the roles that values clarification/preference elicitation (VC/PE) play in the full process of patients' decision support, outlines various approaches to fostering VC/PE, and poses some fundamental and applied research questions about VC/PE. It also argues that, in order to proceed to answer the posed research questions, investigators in the field of patients' decision support require a systematic set of criteria for comparing the performance of different VC/PE techniques.